Canada's technology triangle: Designing a role for regional government in emerging advanced technology based economy. - Levesque, Peter Norman. (University of Ottawa (Canada), 1993)
This thesis examines the activities of the central actors in an emerging advanced technology based economy. The interaction and synergy between university based researchers and advanced technology entrepreneurs has opened significant opportunities for economic renewal and development in Western economies. An understanding of the sociological dynamic between these key players is necessary to the process of harnessing this economic potential. The comparison of this dynamic with the activities of organizations such as Canada's Technology Triangle, will perhaps provide insight into more effective methods of encouraging similar development in other communities.
Keywords: Economics, Commerce-Business.